2023
DOI: 10.3389/fimmu.2023.1127612
|View full text |Cite
|
Sign up to set email alerts
|

GBP2 promotes M1 macrophage polarization by activating the notch1 signaling pathway in diabetic nephropathy

Abstract: BackgroundDiabetic nephropathy (DN) is one of the most common diabetic complications, which has become the primary cause of end-stage renal disease (ESRD) globally. Macrophage infiltration has been proven vital in the occurrence and development of DN. This study was designed to investigate the hub genes involved in macrophage-mediated inflammation of DN via bioinformatics analysis and experimental validation.MethodsGene microarray datasets were obtained from the Gene Expression Omnibus (GEO) public website. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Cholesterol represents an important fatty acid for Mtb as it is a preferred carbon source (32, 34) and contributes to macrophage responses to Mtb including membrane lipid rafts permissive to Mtb uptake (36), modulation of cellular function, and development of foamy macrophages (32, 33, 37, 38). Hippo signaling is involved in pleiotropic activities related to cell proliferation, differentiation, and survival (25) including in macrophages (39). Among these functions, Hippo signaling regulates cholesterol levels through sterol regulatory element-binding proteins (SREBPs) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol represents an important fatty acid for Mtb as it is a preferred carbon source (32, 34) and contributes to macrophage responses to Mtb including membrane lipid rafts permissive to Mtb uptake (36), modulation of cellular function, and development of foamy macrophages (32, 33, 37, 38). Hippo signaling is involved in pleiotropic activities related to cell proliferation, differentiation, and survival (25) including in macrophages (39). Among these functions, Hippo signaling regulates cholesterol levels through sterol regulatory element-binding proteins (SREBPs) (25).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that increased expression of MS4A4A indicated poor prognosis in patients with diabetic nephropathy. 48 The mechanism may involve the participation of the pro-inflammatory M1 macrophage phenotype in the progression of diabetic neuropathy. However, it remains uncertain whether this mechanism has a similar effect in AKI, as current studies do not provide conclusive evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these terms or pathways have also been reported in previous DN-related reviews 9,34,55 or studies of high-throughput methods. 34,56 Next, two machine learning methods were employed to screen potential diagnostic biomarkers of DN in clusters 3, 4, and 6, and five overlapping biomarker proteins (KLK1, CSPG4, PLAU, SERPINA3, and ALB) were identified as key diagnostic biomarkers of DN. The expression of four proteins (KLK1, CSPG4, SERPINA3, and ALB) was verified by ELISA assays, and the results of three proteins were in general agreement with the proteomic results, i.e., KLK1, CSPG4S, and SERPINA3.…”
Section: ■ Discussionmentioning
confidence: 99%